I-DEAS Vibro-Acoustics and RAYON Solvers: Features and capabilities - Assaf, S.; Hamdi, M.A. (Canadian Acoustics, 2000)
I-DEAS Vibro-Acoustics, a computer aided analysis (CAA) software product, was developed from the integration of STRACO’s RAYON Solvers family in the general graphic environment. This CAA engineering tool was composed by an intuitive and easy-to-use graphical user interface (GUI). The tool was dedicated to the analysis of complex three-dimensional vibrating structures coupled to several acoustic fluids. The RAYON solver was based on an unified variational formulation coupling boundary, finite and infinite element methods. Vibro-Acoustics was validated in many real life applications such as aerospace and automotive fields.